Of Rating and Ranking in the Comparison of Fiscal Institutions. Issue 4 (8th August 2017) - Cangiano, Marco
Abstract: Comparing countries' institutional features is a highly judgmental exercise, prone to a number of methodological flaws. But in spite of the difficulties, rating and ranking countries and institutions has been gaining popularity. These comparisons are often based on synthetic indicators that tend to confuse normative aspects (what a government should do) with efficiency/effectiveness arguments (how governments perform). Because of their centrality in determining governments' capacity to deliver efficiently and effectively goods and services while maintaining macro-economic stability, this paper argues that comparative public policy analysis requires a sounder theoretical framework than the one being offered by the existing synthetic indicators. This case is made by analyzing two indices of fiscal rules developed by the European Commission (EC) and the International Monetary Fund (IMF) and showing how they are prone to a normative or best-practice bias, thus ignoring essential contextual factors. The paper thus concludes that the next generation of indicators will have to minimize the use of normative-based best practices and help devise better metrics, with emphasis shifted onto contextual functionality and actual implementation rather than on the effect of announcement, so that substance can prevail over form.